Staphylococcal biofilm on the surface of catheters: Electron microscopy evaluation of the inhibition of biofilm growth by rnaiii inhibiting peptide - de Oliveira, Adilson [UNESP]; Pinheiro-Hubinger, Luiza; Pereira, Valéria Cataneli [UNESP]; Riboli, Danilo Flávio Moraes [UNESP]; Martins, Katheryne Benini [UNESP]; Romero, Letícia Calixto [UNESP]; da Cunha, Maria de Lourdes Ribeiro de Souza [UNESP] (MDPI, 2021)
Staphylococcus aureus and coagulase-negative staphylococci (CoNS) have become the main causative agents of medical device-related infections due to their biofilm-forming capability, which protects them from the host’s immune system and from the action of antimicrobials. This study evaluated the ability of RNA III inhibiting peptide (RIP) to inhibit biofilm formation in 10 strains isolated from clinical materials, including one S. aureus strain, two S. epidermidis, two S. haemolyticus, two S. lugdunensis, and one isolate each of the following species: S. warneri, S. hominis, and S. saprophyticus. The isolates were selected from a total of 200 strains evaluated regarding phenotypic biofilm production and the presence and expression of the ica operon. The isolates were cultured in trypticase soy broth with 2% glucose in 96-well polystyrene plates containing catheter segments in the presence and absence of RIP. The catheter segments were observed by scanning electron microscopy. The results showed inhibition of biofilm formation in the presence of RIP in all CoNS isolates; however, RIP did not interfere with biofilm formation by S. aureus. RIP is a promising tool that might be used in the future for the prevention of biofilm-related infections caused by CoNS.
Keywords: Biofilm inhibition; Biofilm structure; Catheter; Coagulase-negative staphylococci; Quorum sensing; RIP; Scanning electron microscopy; Staphylococcus aureus